2008
DOI: 10.1093/jac/dkn250
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of tigecycline compared with vancomycin or linezolid for treatment of serious infections with methicillin-resistant Staphylococcus aureus or vancomycin-resistant enterococci: a Phase 3, multicentre, double-blind, randomized study

Abstract: Tigecycline is safe and effective in hospitalized patients with serious infection caused by MRSA. There were too few cases of VRE to draw any conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(72 citation statements)
references
References 39 publications
0
71
0
1
Order By: Relevance
“…Tigecycline is another novel antibiotic which many authors believe to be an effective alternative to vancomycin for infections due to MRSA (20,21). Tigecycline resistance among staphylococci has been rarely reported in the literature (22).…”
Section: Discussionmentioning
confidence: 99%
“…Tigecycline is another novel antibiotic which many authors believe to be an effective alternative to vancomycin for infections due to MRSA (20,21). Tigecycline resistance among staphylococci has been rarely reported in the literature (22).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that tigecycline was effective against Gram-positive and Gram-negative bacteria in the Tigecycline Evaluation and Surveillance Trial (TEST) study in 2009 [4]. Florescu et al [10] showed that the rate of success of tigecycline therapy was similar to that of vancomycin in skin-soft tissue infections. In the current study, tigecycline resistance was exhibited by one of the MRSA strains and two of the MRCNS strains.…”
Section: Discussionmentioning
confidence: 99%
“…a These numbers correspond to 2 different randomized controlled trials that were published as one in Clinical Infectious Diseases. 50 45 2005 Corey et al, 39 2010 D'Antonio et al, 55 2004 Florescu et al, 44 2008 Gilbert et al, 72 1991 Jaksic et al, 32 2006 Kureishi et al, 69 1991 Lin et al, 27 2008 Noel et al, 43 2008 Noel et al, 42 2008 Rolston et al, 66 1994 Rolston et al, 58 1999 Rubinstein et al, 38 2001 Rubinstein et al, 50 2011 (0015) …”
Section: Discussionmentioning
confidence: 99%